Analyzing the effects of animated videos on listening skill: A learning style perspective - Atmadja, Dhimas Dwyki; Ningrum, Ary Setya Budhi; Wahyuni, Sri (Universitas Katolik Widya Mandala Surabaya, 2024)
This research aimed to examine the effect of watching animated video on listening skill of students with different learning style. This research used quantitative research as the method. The researcher conducted quasi-experimental. Both classes consist of 30 students. The finding of this study revealed that there is significant difference with the significant value (sig. 0000 < .05; f-obtained > f-table, 26.690 > 4.001). it can be concluded that there is significant difference in listening skill between students who are taught by using watching animated video and that those taught by using story telling for eight grade students of MTsN 6 Blitar. The experimental group achieve better result on their listening test watching animated video is effective in teaching listening for visual, and auditory, but it is not effective for kinesthetic students.